SEJARAH SISTEM PENDIDIKAN MU’ADALAH PONDOK PESANTREN MIFTAHUL MUBTADIIN KREMPYANG NGANJUK - Faricha, Athi Arofatul (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2024)
Pondok Pesantren Miftahul Mubtadiin Krempyang Nganjuk is one example of a Salafiyah pesantren that follows the mu'adalah program for the curriculum of teaching and learning activities. This requires a long struggle considering that in the era after independence there was no special recognition and policy from the government for educational institutions that stood under the auspices of Islamic boarding schools. This research aims to find out the history of mu'adalah -based pesantren education, starting from the pioneering period to obtaining policies from the government of the Republic of Indonesia. This research using qualitative methods seeks to provide systematic data and actual facts related to the historicity to the implementation of the mu'adalah education system in Krempyang boarding school. Problem solving procedures are carried out based on problems that arise after being identified, regarding data collection techniques using observation techniques, interviews, data collection from several library sources. The results of this study indicate that the advancement of technology in this modern era is also a challenge for Krempyang education, so it must carefully prepare the clumps of religious, non-religious and skill sciences and introduce learning technology tools in its education system. Thus, the students are expected to be ready to compete in this era. On the sidelines of this readiness, Krempyang hut also has to go through stage by stage in order to continue to get recognition of mu'adalah status in every educational curriculum accreditation process.